Matrix metalloproteinase (MMP)-2 and MMP-9 activity and localization during ventral prostate atrophy and regrowth - Justulin, L. A. [UNESP] (2010)
Matrix metalloproteinses (MMPs) are enzymes involved in prostatic development, growth, disease-induced tissue remodelling and secretory fluid. Although the prostate function depends upon androgen regulation, the relationship between MMPs and androgen has not been well established. Here, we evaluated MMP-2 and MMP-9 gelatinolytic activity in association with tissue localization during ventral prostate atrophy and regrowth induced by testosterone replacement (TR). Adult male Wistar rats were divided into three experimental groups: control, castrated (CS) and TR 21 days after castration. Ventral prostate (VP) was excised at 3, 5, 7 and 21 days after castration in CS group, and at 3, 5, 7 and 10 days after TR (4 mg/kg/day) in TR group. The VP was dissected, weighed and processed for histology, immunohistochemistry, ultrastructure and zymography analyses. Castration elicited the typical parenchymal atrophy and stromal condensation. TR induced intense epithelial growth towards the stromal space to restore the prostate histoarchitecture. MMP-2 and MMP-9 immunostaining presented intense reaction in CS and TR groups, mainly in the epithelial and endothelial cells. After TR, a strong immunoreaction for MMP-2 was observed in the activated stromal fibroblasts. Zymography showed that MMP-2 and MMP-9 activity, mainly the active form, increased after castration. In contrast, TR induced an additional increase in MMP-2 activity, but not in MMP-9. In conclusion, the overall behaviour of MMP-2 and MMP-9 within the prostate under androgen handling is highly complex, as each glandular compartment and cell type is affected differently by the androgenic status. Prostate regrowth appears to involve a more effective participation of MMP-2 in both epithelial and stromal compartments, while MMP-9 plays a major role in the late prostate atrophy and early regrowth.